Pengenalan Serta Penggunaan Microsoft Eccess pada Perusahaan - Radiyyah, Afif Fathanah Radiyyah; Lubis, Mutia Putri; pasaribu, Yogi Oriena; Nazara, Bobby Sapriman (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to determine the development of Microsoft Access, as well as the history of Microsoft Access. And aims to know the advantages and disadvantages of Microsoft Access Microsoft Access is used mostly by small and medium businesses, in a small organization that may even be used by a large enough company. This research is a research that is collected through interviews and observations. Methods of collecting data or information with the final result of writing. Microsoft Access is commonly used to handle the creation and manipulation of data. Microsoft Access is part of Microsoft Office, included in Professional and higher editions or sold separately.